Abordagem metodológica de investigação das redes inter-firmas sob a perspectiva de estratégia de operações - Gobbo Junior, José Alcides; Vasconcellos, Marcos Augusto de; Salgado, Manoel Henrique; Castro, Rosani de (Revista Gestão da Produção Operações e Sistemas, 2006)
Most studies available about operations strategy have been done under the business unit paradigm (SKINNER, 1969; HAYES e WHEELWRIGHT, 1984; FINE e HAX, 1985; SAMSON, 1991; HILL, 2000). Recently, it has been proposed other extended and up-to-date approach for the operations strategy field, but still working under the business units paradigm (SLACK e LEWIS, 2002) and business units and intra-firm networks paradigm (RUDBERG e OLHAGER, 2003; HAYES et al., 2004). However, nowadays the new paradigm of inter-firm networks competition determines the need for studies under a more holistic approach. This paper presents the results of a field research to verify the validity of the manufacturing strategy theory, which has been developed under a business unit paradigm, under an inter-firm networks perspective. For that, it was necessary to make some adaptations on the existing methodological approaches and theoretical ground for operations strategy, to cope with the specificities presented by inter-firm networks. Under this context, this article presents one methodological approach to extend the scope of two decision areas of operations strategy (vertical integration and facilities) but considering an inter-firm networks perspective. Additionally, the paper presents an example involving a qualitative and exploratory research to illustrate the utility of the proposed approach in an interfirm network. Preliminary results obtained by the survey suggest the validity of the extended model. Key-words: Inter-firm networks; Operations strategy; Network project.